Optic nerve sheath diameter as a non-invasive indicator of intracranial hypertension in traumatic brain injury: correlation with CT head and prognostic implications - Chauhan, Vrinda; Raina, Parul; Kumar, Manuj; Kumar, Sudarshan; Joshi, Amit; Chauhan, Narvir; Kumari, Usha (International Journal of Research in Medical Sciences, 2023)
Background: Ultrasound guided measurement of optic nerve sheath diameter (ONSD) is an emerging non invasive bedside tool that is being used to detect raised intracranial pressure (ICP) in patients with traumatic brain injury(TBI). Early detection of raised ICP can guide in the timely management of such patients with raised ICP due to TBI. Methods: A prospective, observational, open labelled study planned with a 30 patients of TBI of both genders, aged between 18 to 70 years. ONSD readings were taken 3 times a day for three days from the time of admission with portable SonoSite ultrasound machine. Data was expressed as mean ±standard deviation. Values were compared using T test and P value was calculated. Results: Highest reading recorded in patients with GCS <8 was 6.26±0.73 in comparison to 5.38±0.56 (p=0.001) in patients with GCS >8. Highest reading of ONSD correlating with a positive CT finding at admission was 6.22±.81 and was 5.46±.57 (p=0.006) in patients with negative findings on CT. ROC curve with average cut off of 6 mm correlated with positive CT findings with sensitivity of 80%, specificity of 70% and negative predictive value of 87% was found. Conclusions: Ultrasound-guided ONSD monitoring shows promise for diagnosing intracranial hypertension in traumatic brain injury. Correlations with CT, GCS, and outcomes emphasize its clinical relevance, warranting further validatio.